Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Sepeda Motor Honda Pada PT Daya Adicipta Wisesa Maumbi Manado - Rumansara, Johanes; Montolalu, John; Sumampouw, Harry (Sam Ratulangi University, 2015)
Abstract: This study aims to determine how far the quality of service to customer satisfaction Honda at PT Wisesa Adicipta by taking the respondents were 60 respondents . The analysis method used in this research is quantitative method with the approach of simple correlation analysis and simple regression. Results of simple correlation analysis is r = 0.88 this indicates that if the quality of service rise, customer satisfaction will go up anyway. The degree of correlation is in the category of high and after having tested its significance, the showed very significant. Deteriminasi coefficient r2 = 77 %, satisfaction factors determined by the quality of service and the rest is determined by other factors. With a simple regression analysis obtained Y = 5.07 + 0,75X, this may imply that each additional one scale on the quality of service will result in additions to the customer satisfaction scale of = 0.75. Thus evident that the quality of service has an influence on customer satisfaction . Based on these results, the researchers suggested that the leadership continue to observe and pay attention to the elements of service quality variables that have not been touched in this study and in order to maintain the quality of services that exist today, so give satisfaction to customers .Keywords : Service Quality, Customer Satisfaction